Siyasah Shari'ah and the Discretionary Actions of the Ruler: Examining the Work of al-Qarafi in al-Tamyiz and al-Subki in al-Fatawa in Classical Islam - Mohd Zakhiri Md Nor (Sharia and Law Faculty, 2020)
SharÄ«Ê¿ah law is a revealed law and the ruler applies the SiyÄsah SharÄ«Ê¿ah in administering the state according to Allah ordained. The question is whether this discretion of the ruler remains open in exercising the SiyÄsah al-SharÄ«Ê¿ah. This paper focuses on the application of siyÄsah syarÄ«yyah and discretionary actions of ruler in classical Islam. It is also to examine the work of al-QarÄfÄ« in TamyÄ«z and al-SubkÄ« in FatÄwÄ al-SubkÄ« in classical Islam. The paper first outlines the nature of siyÄsah al-SharÄ«Ê¿ah from SharÄ«Ê¿ah perspective. The next part of the paper examines the roles of the ruler in exercising the siyÄsah al-SharÄ«yyah. The context of the study is the work of al-QarÄfÄ« and al-SubkÄ« in Classical Islam. The paper concludes by outlining several recommendations for determining the parameters of the application of siyÄsah al-SharÄ«Ê¿ah and discretionary actions of ruler in the contemporary Islamic state. The methodology adopted in the research is purely qualitative, engaging in doctrinal archival research of classical literatures and cases on the discretion actions of ruler in the application of siyÄsah al-SyarÄ«Ê¿ah. Since there is scarcity of resources on the subject matter, this study is deemed to be significant in filling in the gaps of the application of siyÄsah al-SyarÄ«yyah and discretionary actions under the SharÄ«Ê¿ah laws.